2023
DOI: 10.3390/en16062830
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Most Promising Second-Life Applications for Automotive Lithium-Ion Batteries Considering Technical, Economic and Legal Aspects

Abstract: Electric vehicle (EV) batteries, i.e., currently almost exclusively lithium-ion batteries, are removed from the vehicle once they no longer meet certain requirements. However, instead of being disposed of or recycled, the removed batteries can be used in another, less demanding application, giving them a “second life”. Research in the field of second-life batteries (SLBs) is still at an early stage and, to better understand the “second life” concept and the related challenges, potential second-life application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…Many studies present several practical applications of SLB in various fields like load leveling, renewable firming, backup systems, etc. [104] concluded that the best possible application for SLB at present is in the renewable firming field in the grid application and the automated guided vehicles in the mobility application.…”
Section: Market Opportunities Of Slbmentioning
confidence: 99%
“…Many studies present several practical applications of SLB in various fields like load leveling, renewable firming, backup systems, etc. [104] concluded that the best possible application for SLB at present is in the renewable firming field in the grid application and the automated guided vehicles in the mobility application.…”
Section: Market Opportunities Of Slbmentioning
confidence: 99%
“…Boat [76] Electric golf cart and motorcycle [77] Heavy duty [78] Mobile charging station [79] Compared to stationary ones, a limited number of articles have presented performance requirements for mobile uses [48,80]. To fill this gap in the literature, the requirements for certain uses were estimated on the basis of usage profiles shared in the literature [81].…”
Section: Mobile Application Referencementioning
confidence: 99%
“…The scientific literature on the battery passport and the assessment of its suitability for a second life in a particular application is sparse. Montes et al [47] and Michelini et al [48] have proposed lists of information that could be useful in making a decision on the suitability of a battery for a particular application, without however describing methods for obtaining this information. Beckers et al presented an algorithm for determining the efficiency of an end-of-life automotive battery [39].…”
mentioning
confidence: 99%
“…The other option is a second application in SLB [10,11]. An SLB can be applied to semior entirely stationary systems to store energy from solar and wind-solar farms [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, SLBs can supply power for low-speed vehicles such as golf carts, trucks, lifts, automated guided vehicles (AGVs), or others [10,15].…”
Section: Introductionmentioning
confidence: 99%